The Effect of Cigarette Smoking during Pregnancy on Endocrine Pancreatic Function and Fetal Growth: A Pilot Study - Lockhart, Fatima; Liu, Anthony; Champion, Bernard Linton; Peek, Michael John; Nanan, Ralph Kay Heinrich; Poulton, Alison Sally (Frontiers in Public Health, 2017)
Introduction: Cigarette smoking in pregnancy is a common cause of foetal growth restriction. We aimed to investigate endocrine pancreatic function of mother-infant dyads in relation to cigarette smoking, as a possible mechanism for the poor foetal growth. Methods: Prospective study of smoking mothers (10 cigarettes or more per day, self-reported to the midwife) and non-smoker control mothers during their first pregnancy. Insulin, glucose, C-peptide, HbA1C, fructosamine, prolactin, serotonin and cortisol were measured in maternal blood at 24-26 weeks and in umbilical cord blood at birth. Cotinine was also measured in cord blood. Results: Of 37 smokers and 36 non-smokers recruited, cord blood was obtainable from 38 babies (19 in each group). In utero cigarette exposure was associated with lower birthweight (3035±490g versus 3405±598, p=0.005), with linear modeling of the smoking cohort showing a 41g reduction for every increase of 1 cigarette smoked per day (95%CI -71 to -11g, p=0.010). There were no differences between groups in indices of maternal or perinatal endocrine pancreatic dysfunction. Heavier smoking independently correlated with higher maternal fasting levels of glucose (p=0.044) and C-peptide (p=0.011). We did not observe any significant associations between the daily number of cigarettes and any of the cord blood parameters. We also looked for differences between cohorts based on infant gender. Serotonin levels were higher in smoking mothers with male foetuses (p=0.01 to p=0.004). Conclusions: Endocrine pancreatic dysfunction does not appear to be a major contributing factor to nicotine associated foetal growth restriction. The higher serotonin levels in smoking mothers carrying male infants is of uncertain significance but could be a manifestation of gender differences in susceptibility to the long-term effects of cigarette smoking.